Combustion engines development mixture formation, combustion, emissions and simulation - Merker, Gunter P. [ed.]; Schwarz, Christian [ed.]; Teichmann, Rudiger [ed.] (Berlin Springer, 2012)
Combustion Engines Development nowadays is based on simulation, not only of the transient reaction of vehicles or of the complete driveshaft, but also of the highly unsteady processes in the carburation process and the combustion chamber of an engine. Different physical and chemical approaches are described to show the potentials and limits of the models used for simulation.
Keywords: Internal combustion engines -- Design and construction